MOLECULAR CHARACTERIZATION OF BEGOMOVIRUS INFECTING YARD LONG BEAN (Vigna unguiculata SUBSP. sesquipedalis L.) IN JAVA, INDONESIA - Sari Nurulita; Sri Hendrastuti Hidayat; Kikin Hamzah Mutaqin; John Thomas (SEAMEO BIOTROP, 2015)
Begomovirus has been identified as one of the causal agents associated with yellow mosaic disease in yardlong bean (Vigna unguiculata subsp. sesquipedalis (L.)) in Java. Previous studies reported that Begomovirus has infected several Leguminosae species in South Asia, and several Begomoviruses have also been reported to infect important crops in Indonesia based on nucleotide sequence characterization. This study was conducted to identify and characterize Begomovirus isolated from yardlong bean samples in Java based on specific genomic features of the Common Region. Samples were collected from yardlong bean fields in Central Java (Tegal, Magelang, and Klaten), Yogyakarta (Sleman), and West Java (Bogor and Subang); viral detection was performed using I-ELISA, PCR, and sequencing; and molecular characterization was conducted using BioEdit v.7.0.5 and MEGA 6.06 software. Yellow mosaic disease was observed in nearly all surveyed fields, and infection of Potyvirus and Begomovirus was detected either as single or mixed infection. PCR results confirmed Begomovirus infection in samples from Tegal, Klaten, Magelang, Subang, and Bogor. Sequence analysis revealed that the virus infecting yardlong bean was Mungbean Yellow Mosaic India Virus (MYMIV) and shared close genetic similarity with isolates from Bangladesh, India, Pakistan, and Nepal. Further analysis revealed conserved regions surrounding the Common Region, including the “TATA box” sequence, hairpin-loop structure, repetitive sequences, and the conserved nonanucleotide TAATATTAC. This study provides the first report of MYMIV infection in Indonesia.